2022
DOI: 10.3389/fphys.2022.927163
|View full text |Cite
|
Sign up to set email alerts
|

Role of Inflammation in Cardiac Remodeling After Acute Myocardial Infarction

Abstract: Atherosclerosis is defined as an inflammatory disease. Low-grade inflammation is present in all phases of the cardiovascular continuum, since the establishment of cardiovascular risk factors and ischemic heart disease until cardiovascular events, such as myocardial infarction, heart failure and death. Not all inflammatory pathways are linked to cardiovascular outcomes, and thus, not all anti-inflammatory approaches decrease cardiovascular events. The most common cause of ventricular remodeling and heart failur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…Atherosclerosis is also a chronic inflammatory disease, as an inflammatory response accompanies its onset. 180 Macrophages are one of the cells responsible for atherosclerosis; they form foam cells by phagocytosing lipid droplets and accelerating the progression of atherosclerosis. 181 , 182 Basu et al 183 reported that macrophage-specific deletion of RPL13 increases the susceptibility of ApoE knockout mice to high-fat diet-induced atherosclerosis.…”
Section: Ribosomes and Cardiovascular Diseases (Cvds)mentioning
confidence: 99%
“…Atherosclerosis is also a chronic inflammatory disease, as an inflammatory response accompanies its onset. 180 Macrophages are one of the cells responsible for atherosclerosis; they form foam cells by phagocytosing lipid droplets and accelerating the progression of atherosclerosis. 181 , 182 Basu et al 183 reported that macrophage-specific deletion of RPL13 increases the susceptibility of ApoE knockout mice to high-fat diet-induced atherosclerosis.…”
Section: Ribosomes and Cardiovascular Diseases (Cvds)mentioning
confidence: 99%
“…Previous studies have shown a causal relationship between IL‐6 and cardiovascular disease 119 . Additionally, IL‐6 has been associated with ventricular dysfunction 120 . The meta‐analysis revealed that levosimendan has the potential to reduce IL‐6 levels.…”
Section: Discussionmentioning
confidence: 99%
“…LV remodeling is a process in which the heart adapts to mechanical, neurohormonal, and inherited changes by regulating the size, shape, and function of the ventricle. It is commonly observed in infarcted hearts [ 4 ]. Adverse LV remodeling following MI involves various processes, including the transformation of LV geometry, myocardial fibrosis, a shift in energy metabolism, neurohormonal activation, and inflammation.…”
Section: Role Of Inflammation In Myocardial Infarctionmentioning
confidence: 99%
“…After myocardial infarction, ventricular remodeling or recurrent ischemic events are both reported to be associated with inflammation [ 4 ]. In particular, during the early phase of cardiac injury, inflammation plays a crucial role in determining the extent of myocardial injury, including cardiomyocyte necrosis and the degradation of extracellular matrix components.…”
Section: Introductionmentioning
confidence: 99%